The Influence of Mental Health Education Programs in Improving Patients' Quality of Life - Penti Dora Yanti; Septin Maisharah karyono; Sayang Ajeng Mardhiyah; Rita Rahayu; Emdat Suprayitno (Journal of World Future Medicine, Health and Nursing, 2024)
Mental health is a vital aspect of an individual's well-being that has a direct impact on their quality of life. However, there are still many patients who experience mental health problems that are undiagnosed or not well-managed. Therefore, mental health education programs are important to improve understanding and management of patients' mental health conditions. This study aims to evaluate the effect of mental health education programs on improving patients' quality of life. With a focus on understanding their condition, stress management abilities, and skills in dealing with daily challenges related to mental health. The research method used is quantitative and qualitative with a prospective intervention study. Data was collected through questionnaires. The results of this study indicate an increase in patients' understanding of their mental health conditions, as well as an improvement in their ability to manage stress and related daily challenges. Apart from that, the patient's quality of life also improves after participating in the mental health education program. The conclusion of this research is that mental health education programs have a positive impact on the quality of life of patients with mental health disorders. Increased understanding, stress management skills, and feelings of ability to face daily challenges help patients feel more able to manage their mental health conditions more effectively, which in turn improves their overall quality of life. This research provides a strong basis for continuing and developing mental health education programs as an integral part of the care of patients with mental health disorders. It is hoped that ongoing efforts in outreach and education about mental health will strengthen understanding and support for patients, as well as improve their clinical outcomes and quality of life in a sustainable manner.